2019
DOI: 10.1364/oe.27.027891
|View full text |Cite
|
Sign up to set email alerts
|

Coherent beam combining of high power quasi continuous wave tapered amplifiers

Abstract: We demonstrate coherent beam combining of four high brightness tapered amplifiers in pulsed, quasi continuous wave (QCW) operation, seeded by a 976 nm laser diode. The maximum power of 22.7 W was achieved with > 64 % combining efficiency in a close to diffraction limited beam. We discuss turn-on dynamics of tapered amplifiers operated in pulsed mode in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Coherent beam combining is difficult to apply for the complex system. Incoherent beam combining technology is the main method to realize high-power lasers [10][11][12][13][14][15]. Spectral beam combining which was proposed by MIT in 2000 is the most promising technology with the advantages of high beam quality (close to that of single emitter) and high outpower [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Coherent beam combining is difficult to apply for the complex system. Incoherent beam combining technology is the main method to realize high-power lasers [10][11][12][13][14][15]. Spectral beam combining which was proposed by MIT in 2000 is the most promising technology with the advantages of high beam quality (close to that of single emitter) and high outpower [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, Thales Research and Technology in France reported the coherent beam combining of 5 quantum-cascade lasers by a binary phase or Dammann grating [4]. All of the above solutions are coherent beam combining, which requires a high degree of coherence between different channel lasers and is hard to accomplished experimentally, especially when the number of lasers is large [5][6][7][8][9]. The feasibility of a spectral beam combining (incoherent beam combining) scheme was proposed by Christopher C. Cook et al at Lincoln Laboratory in 1999 [10] and was experimentally achieved for a semiconductor laser array in 2000, where the combined beam quality was almost identical to that of the single emitter [11], and in the same year, they have also successfully achieved spectral beam combining of 11-channel lasers [12].…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true in fiber lasers, where the high-energy pulses are confined to a small fiber core. To overcome this problem, many advanced techniques have been demonstrated, among which is coherent beam combining [14,15], pulse stacking [16], the use of tapered fiber amplifiers [17,18] and the use of optical fibers with large core diameters [19,20]. Although these systems offer some outstanding results in terms of power scaling, their relative complexity hinders their applicability in industrial laser applications.…”
Section: Introductionmentioning
confidence: 99%